2005
DOI: 10.1097/01.brs.0000170298.89145.b4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trunk Balance in Thoracic Scoliosis

Abstract: In patients with thoracic idiopathic scoliosis, if the CB and thoracic AVT values are known, then the LTS can be reliably estimated. The use of correct terminology for describing trunk balance and CB is important if valid comparisons of spinal deformity literature are desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 21 publications
0
16
0
7
Order By: Relevance
“…However, their findings were only reliable in patients with marked coronal imbalance, which does not happen to be the case for the majority of patients with AIS [6]. Although Luk et al [10] measured postoperative trunk shift in patients with Lenke type 1 curves, the authors did not further analyze their data in regard to prevalence, incidence, or risk factors for postoperative decompensation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, their findings were only reliable in patients with marked coronal imbalance, which does not happen to be the case for the majority of patients with AIS [6]. Although Luk et al [10] measured postoperative trunk shift in patients with Lenke type 1 curves, the authors did not further analyze their data in regard to prevalence, incidence, or risk factors for postoperative decompensation.…”
Section: Discussionmentioning
confidence: 91%
“…Numerous studies have used the C7P-CSVL distance as an outcome tool for coronal balance after surgical treatment for AIS [3][4][5][6][7], but there is a paucity of data commenting on the postoperative trunk balance and/or trunk shift in AIS. The purpose of this study is to analyze postoperative trunk balance in AIS patients with a Lenke type 1 or 2 curve from a prospective multicenter database.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the thorax may be evaluated with 2 methods, the measurement of lateral trunk shift or the apical vertebra translation. In their study, Richards et al17) have evaluated the relation among lateral trunk shift, thoracic apical vertebra translation, and the coronal balance. They have reported that the sum of coronal balance and the apical vertebra translation is related with lateral trunk shift.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the lowest instrumented vertebra should be as proximal as possible to preserve lumbar motion, but it should be distal enough to avoid trunk imbalance. The level of the lowest instrumented vertebra and the amount of sufficient correction are still controversial8141720). It is also uncertain if coronal imbalance may develop in a spinal column, totally corrected with a short segment fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, coronal balance (CB) is measured and quantified by the perpendicular distance between the coronal C7 plumbline (C7PL) and the central sacral vertical line (CSVL), with a value [20 mm being defined as imbalance [4]. Numerous studies have used the C7PL-CSVL distance as an assessment tool for surgical outcomes of AIS [5][6][7][8], but there is a paucity of data specifically addressing the postoperative CB in AIS [9], especially the ultimate CB after a long period of follow-up.…”
Section: Introductionmentioning
confidence: 99%